Bibliometric analysis using R on corporate governance mechanisms / Hamizah Hassan - Hassan, Hamizah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This research intended to shed light on existing and future research trends of corporate governance mechanisms by offering a full bibliometric mapping through descriptive and network analyses of corporate governance studies. The multi-perspective research articles on corporate governance mechanisms, spanning from 1996 to the third quarter of 2022, were identified and analysed using Biblioshiny, a Bibliometrix R software. Prior to the analysis, the selected articles were scanned, cleaned, and harmonised. Overall, findings from this bibliometric study provided important information on current and future corporate governance publications. This included information on highly cited documents, most productive contributors, most frequently used keywords, most productive countries and sources, network analysis data on co-occurrence networks, and themes mapping information on corporate governance mechanisms studies. The Scopus database was used as the search strategy to find relevant literature. As an implication, this study provides useful findings to guide other researchers in mapping current and future studies on corporate governance mechanisms. To the researcher’s knowledge, this is the first Biblioshiny-based bibliometric analysis conducted on corporate governance mechanisms, with 282 documents analysed. The review emphasises on annual publication trends, the most productive authors, publications, countries, institutions, and sources, leading to future research priorities.